2001
DOI: 10.1164/ajrccm.164.11.2003151
|View full text |Cite
|
Sign up to set email alerts
|

The Cost Effectiveness of Early Treatment with Fluticasone Propionate 250 μ g Twice a Day in Subjects with Obstructive Airway Disease

Abstract: In a two-stage detection program, subjects with signs of obstructive airway disease were selected from a random sample of the general population. Subjects (n = 82) were randomly assigned to either fluticasone propionate 250 microg twice a day or placebo twice a day via pMDI in a 1-yr, double-blind trial if they met criteria for persistent airway obstruction, increased bronchial hyperresponsiveness, or a rapid decline in FEV(1). Main outcome measures were postbronchodilator FEV(1), quality-adjusted life years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 42 publications
0
31
0
1
Order By: Relevance
“…Test-retest reliability intra-class correlation coefficients of 0.73-0.95 and internal consistency reliability ranging 0.53-0.90 (Cronbach's alpha) have been reported [117,165,[448][449][450][451].…”
Section: Chronic Respiratory Questionnairementioning
confidence: 99%
“…Test-retest reliability intra-class correlation coefficients of 0.73-0.95 and internal consistency reliability ranging 0.53-0.90 (Cronbach's alpha) have been reported [117,165,[448][449][450][451].…”
Section: Chronic Respiratory Questionnairementioning
confidence: 99%
“…While most previous economic evaluations of asthma therapies have used either the cost per symptom day avoided or the cost per 0.5 unit change on the AQLQ(S) as a measure of cost effectiveness [17], only a limited number of studies have measured effectiveness in terms of QALYs [18][19][20][21][22][23]. A recent study, exploring the relationship between asthma control and HRQL, found that the EQ-5D was able to distinguish across levels of control [23].…”
Section: Introductionmentioning
confidence: 99%
“…32 However, at least 6 months of treatment may be required to demonstrate the expected benefits in health status with pharmacologic therapy. 23,38 Rescue albuterol use was slightly lower (range, Ϫ 0.1 to Ϫ 0.4 puffs per day) in the active-treated group, compared to placebo. It is possible that the concomitant use of long-acting ␤-agonists and ipratropium bromide may have limited the utility of this end point.…”
Section: Discussionmentioning
confidence: 94%